Localization of WSN Using CDPSO with CRB Algorithm: Improving Localization in WSN using CDPSO with CRB Algorithm (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Localization is the procedure of count on location of node position. In WSN, sensors deployed randomly and found the location of nodes is difficult. In this network, the nodes, knowing their location is important for indoor applications. In this application, the signals are affected by various factors such as noise, multipath, LOS etc. This impact on inaccurate location information of node, which leads to finding path to the destination node, is difficult. Localization system consists of three stages Measurement of distance, Calculation of Position, Applying localization algorithm. Various methods will be implemented in each phase of localization procedure to improve the performance. In this paper, CDPSO algorithm with CRB for localization of cooperative WSN is proposed. Simulation tests have been conducted with various conditions. Comparisons made between proposed algorithm and existing algorithms like PSO, LMS, RLS and GPS algorithm in terms of position accuracy, CDF, complexity and MSE. From the comparison results it is noticed that proposed technique performs better than other algorithms. The proposed solution selects the best reference nodes using CRB and applying localization algorithms